2021
DOI: 10.1007/s10055-021-00516-3
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of virtual reality training in antromastoidectomy simulation

Abstract: Virtual reality (VR) may be a good alternative for cadaveric temporal bone surgical dissection courses, which are an important part of otolaryngology resident’s training. The aim of the study was to assess the VR temporal bone surgery simulator in an antromastoidectomy simulation. The VR system was based on the Geomagic Touch Haptic Device from 3D System. The research was designed as a prospective study, with three sessions of VR simulation training. The group of four ENT specialists unexperienced in otosurger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Also, it was identified that VR fostered active learning. Mickiewicz [ 40 ] evaluated the VR impact on otolaryngology resident’s training. VR training allowed the participants to significantly improve virtual antromastoidectomy performance and resulted in a shortening surgery duration and number of mistakes made.…”
Section: Theorethical Frameworkmentioning
confidence: 99%
“…Also, it was identified that VR fostered active learning. Mickiewicz [ 40 ] evaluated the VR impact on otolaryngology resident’s training. VR training allowed the participants to significantly improve virtual antromastoidectomy performance and resulted in a shortening surgery duration and number of mistakes made.…”
Section: Theorethical Frameworkmentioning
confidence: 99%
“… 23,27 The remaining 95% ( n = 38) included data categorized as level‐2, many of which also included level‐1 data (Data S2), with none reaching level‐3 or 4 (Table III). Analysis of learner reaction (level‐1) was based on interviews or subjective ratings and survey comments 23,27,31,32,39,42,43,61 . Level‐2 evaluation comprised of knowledge performance, cognitive load, and most frequently, skill performance.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of learner reaction (level-1) was based on interviews or subjective ratings and survey comments. 23,27,31,32,39,42,43,61 Level-2 evaluation comprised of knowledge performance, cognitive load, and most frequently, skill performance. Knowledge performance was evaluated using researcher-developed assessments including both closed and open-ended questions.…”
Section: Educational Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, virtual reality (VR) technology has developed rapidly. The simulator based on VR has become an important way in learning and training, and has a wide range in many fields [1]- [4]. If VR can be better applied to navigation training and teaching, it will effectively solve the above problems.…”
Section: Introductionmentioning
confidence: 99%